Does Vibrio Vulnificus Present a Health Threat to Canadians? - Stanislava Stavric; Barbara Buchanan (Canadian Journal of Infectious Diseases)
OBJECTIVE: To review recent data on Vibrio vulnificus and its properties, characteristics of disease and epidemiology, sources of infection, population at risk, infectious dose, documented cases of infection and health risk from V vulnificus infection in Canada.